Hypovitaminosis D Among Patients Admitted With Hip Fracture to a Level-1 Trauma Center in the Sunny Upper Egypt: Prevalence and Associated Correlates. (September 2016) - Farouk, Osama; Mahran, Dalia G.; Said, Hatem G.; Alaa, Mohamed M.; Eisa, Amr Atef; Said, Galal Z.; Rashed, Heba; Ez-Eldeen, Azza
Introduction: Despite abundant sunshine, hypovitaminosis D is common in the Middle East. The aim of this study was to determine the prevalence of hypovitaminosis D and related correlates among patients with hip fracture in Assiut University Hospitals in Upper Egypt. Materials and Methods: A cross-sectional study was carried out in 133 patients with hip fracture, aged 50 years and older, admitted to Trauma Unit of Assiut University Hospitals, from January through December 2014. Patients were selected by systematic random sampling. Serum 25-hydroxy vitamin D level was measured by enzyme-linked immunosorbent assay; bone mineral density (BMD) by dual-energy X-ray absorptiometry. Weight and height measurements were used for body mass index (BMI) calculation. Results: Patients' median age was 70 years (range: 50-99); 51.9% were females. Osteoporosis (femoral neck T score: <−2.5 standard deviation) prevalence was 72.2%. Of all patients, 60.9% had vitamin D deficiency (<20 ng/mL); 15.8% reported vitamin D inadequacy (from 20 to 29 ng/mL) and vitamin D levels were normal in 23.3% (>30 ng/mL). According to univariate analysis, vitamin D deficiency was significantly associated with obesity ( P = .012) and low T scores of the femoral neck ( P = .001), L2 ( P = .021), L3 ( P = .031), L4 ( P = .012), and the greater trochanter ( P < .001). In a multivariable logistic regression model, high BMI and low BMD of the femoral neck and greater trochanter were associated with hypovitaminosis D. Conclusion: Prevalence of hypovitaminosis D is high among patients with hip fracture and associated with low BMD and high BMI. Increasing awareness about prevention as well as detection and treatment of vitamin D deficiency is recommended.